Comparative Effectiveness of Risankizumab vs Other Biologics in Crohn’s Disease: Long-Term and Quality-of-Life Outcomes after Inadequate Response to Prior Therapy - Monika Babczyńska; Agnieszka Buliszak; Piotr Marcjasz; Anna Bioły; Agnieszka Borończyk; Piotr Zając (Quality in Sport)
Introduction and Purpose: